2011
DOI: 10.1177/1362361310387804
|View full text |Cite
|
Sign up to set email alerts
|

Peer interaction patterns among adolescents with autistic spectrum disorders (ASDs) in mainstream school settings

Abstract: The aim of the current study was to document the peer interaction patterns of students with autistic spectrum disorders in mainstream settings. Structured observations of a group of 38 adolescents with ASD drawn from 12 mainstream secondary schools were conducted over a two-day period and data compared with those of school, age, and gender matched comparison groups of 35 adolescents with dyslexia and 38 with no identified special educational needs (the ASD and dyslexia groups were also matched on SEN provision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 36 publications
(38 reference statements)
8
120
2
4
Order By: Relevance
“…Drawing upon three key theoretical frames (Bronfenbrenner 2005;Lewis and Norwich 2005;Humphrey and Symes 2011), we have highlighted compelling evidence that those on the autism spectrum are considerably more likely to be bullied than those with other or no SEND (e.g. Kloosterman et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Drawing upon three key theoretical frames (Bronfenbrenner 2005;Lewis and Norwich 2005;Humphrey and Symes 2011), we have highlighted compelling evidence that those on the autism spectrum are considerably more likely to be bullied than those with other or no SEND (e.g. Kloosterman et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Conceivably, one reason for rejecting difference might be a lack of awareness on the part of peers about the underlying reasons for the difference -namely the ASD. This explanation is supported by previous research by Humphrey and Symes (2011) in which they observed 38 adolescents with ASD over a two-day period and compared with those of school, age, and gender matched comparison groups of 35 adolescents with dyslexia and 38 with no identified special educational needs. Humphrey and Symes (2011) found that if a peer group had a lack of awareness and understanding of ASD this led to a reduced acceptance of difference and increased bullying and social rejection for students with ASD.…”
Section: Chapter Summarysupporting
confidence: 74%
“…This explanation is supported by previous research by Humphrey and Symes (2011) in which they observed 38 adolescents with ASD over a two-day period and compared with those of school, age, and gender matched comparison groups of 35 adolescents with dyslexia and 38 with no identified special educational needs. Humphrey and Symes (2011) found that if a peer group had a lack of awareness and understanding of ASD this led to a reduced acceptance of difference and increased bullying and social rejection for students with ASD. They developed the 'reciprocal effects peer interaction model', which showed that social rejection of students with ASD led to increased isolation and loneliness (Humphrey & Symes, 2011, p. 400).…”
Section: Chapter Summarysupporting
confidence: 74%
“…Teachers felt that they were required to facilitate interaction between students with autism and their peers (Soto-Chodiman, Pooley, and Taylor 2012). The tendency for students with autism to behave differently from their peers and their difficulties or lack of skills in responding to social situations resulted in students with autism experiencing isolation, teasing and bullying, which were perceived by students, parents and education professionals to be frequently encountered by students with autism (Gray and Donnelly 2013;Hedges et al 2014;Humphrey and Lewis 2008;Humphrey and Symes 2011;Johansson 2014;Saggers, Hwang, and Mercer 2011;Sciutto et al 2012) UNESCO (1994), various international declarations enacted on inclusive education have given the rights to all children to access education in mainstream settings. Research had demonstrated that youngsters with disabilities displayed better social skills and educational success when they found out in the same environment with their normally developing students (Koegel et al2011).…”
Section: Teacher and Peers Experiences In Inclusive Settingsmentioning
confidence: 99%